Pengaruh Product Involvement Dan Word of Mouth Terhadap Keputusan Pembelian Kosmetik Asal Korea Merek Etude the House - Adam Hadi Kusnadi; M. Yamin Siregar; Teddi Pribadi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
The purpose of this study was to determine and analyze the Effect of involvement products and word of mouth on purchasing Decisions of Korea Etude House Medan Cosmetics. The research method used is associative research, where variables are measured on a likert scare. The method of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were all consumers Of Etude House Cosmetics products in medan, medan totaling 114 people sampling with saturated sampling method or better known as the census. In this study the total population is relatively small as many as 11 people. Data processing using SPSS software version 23, with descriptive analysis and hypothesis testing multiple regression analysis. The results showed that: (1) partially product involvement variables influenced the purchasing decision of Korea Etude House Medicinal Products (2) partially word of mouth variables influenced the Purchasing Decisions Of Korea Etude House Medicinal Products, (3) Simultaneously there were positive influences and significant between product Involvement and Word Of Mouth variables influences the Etude House Medan Korean Cosmeticts Product Purchasing Decision.